1999
DOI: 10.1023/a:1006291607871
|View full text |Cite
|
Sign up to set email alerts
|

Antimetastatic effect of desmopressin in a mouse mammary tumor model

Abstract: We have investigated the effects of desmopressin (DDAVP), a synthetic analog of the natural hormone vasopressin, on experimental lung colonization of mammary tumor cells using a syngeneic BALB/c mouse model. Coinjection of DDAVP (1-2 microg/kg body weight) at the time of i.v. inoculation of F3II carcinoma cells or LM3 adenocarcinoma cells significantly inhibited the formation of experimental lung metastases. In both cases, the number of pulmonary nodules was reduced about 70%. Inhibition of metastasis was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 16 publications
2
46
0
Order By: Relevance
“…Taylor et al demonstrated that the V2-specific agonist dDAVP did not inhibit AVP binding to Mcf7 cells [11], although later work has shown that these cells do express the V2 receptor [16]. dDAVP can have an anti-metastatic effect on breast cancer cells in mouse tumor models [18,38], however those studies indicate that dDAVP did not have a cytotoxic effect on the tumor cells. Additionally, human V1a receptor expressing CHO cells displayed increased thymidine uptake in response to AVP, while human V2 receptor expressing CHO cells displayed a reduction of thymidine uptake [60].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Taylor et al demonstrated that the V2-specific agonist dDAVP did not inhibit AVP binding to Mcf7 cells [11], although later work has shown that these cells do express the V2 receptor [16]. dDAVP can have an anti-metastatic effect on breast cancer cells in mouse tumor models [18,38], however those studies indicate that dDAVP did not have a cytotoxic effect on the tumor cells. Additionally, human V1a receptor expressing CHO cells displayed increased thymidine uptake in response to AVP, while human V2 receptor expressing CHO cells displayed a reduction of thymidine uptake [60].…”
Section: Discussionmentioning
confidence: 98%
“…When Mcf7 and Skbr3 cells were cultured in the presence of 10 nM SR49059 alone, they displayed similar growth as untreated control cells (not shown). The V2 agonist dDAVP appears to inhibit breast cancer cell metastasis [18,38], and the V2 receptor may mediate anti-proliferative effects [17]. Cells were exposed to 10 nM dDAVP alone or in the presence of the V2 antagonist SR121463 and their proliferation was measured.…”
Section: A Vp-induced Erk1/2 Activation and Cell Proliferationmentioning
confidence: 99%
“…This peptide has hemostatic and antidiuretic effects, and has been used in the management of diabetes insipidus (Manucci, 1997). Interestingly, DDAVP inhibited experimental lung metastasis of mammary tumor cells in a mouse model (Alonso et al, 1999). In human breast cancer cell lines, DDAVP exhibits moderate antiproliferative effects (Iannucci et al, 2011).…”
Section: Conventional Therapies and New Treatment Strategiesmentioning
confidence: 99%
“…Desmopressin is a safe and effective hemostatic agent in patients with von Willebrand disease, hemophilia A, and other bleeding disorders [4,5]. Recent reports suggest that desmopressin inhibits tumor progression and metastasis in in vivo models [6][7][8]. Although these studies suggest that desmopressin has both anti-tumor and anti-metastatic effects on cancer cells, the mechanism of action has not been determined.…”
Section: Introductionmentioning
confidence: 99%